Elevated basal AMP-activated protein kinase activity sensitizes colorectal cancer cells to growth inhibition by metformin - Kaitlin R. Morrison; Tingting Wang; Kuan Yoow Chan; Eleanor W. Trotter; Ari Gillespie; Michael Z. Michael; Jonathan S. Oakhill; Iain M. Hagan; Janni Petersen (Open Biology, 2023)
Expression and activity of the AMP-activated protein kinase (AMPK) α1 catalytic subunit of the heterotrimeric kinase significantly correlates with poor outcome for colorectal cancer patients. Hence there is considerable interest in uncovering signalling vulnerabilities arising from this oncogenic elevation of AMPKα1 signalling. We have therefore attenuated mammalian target of rapamycin (mTOR) control of AMPKα1 to generate a mutant colorectal cancer in which AMPKα1 signalling is elevated because AMPKα1 serine 347 cannot be phosphorylated by mTORC1. The elevated AMPKα1 signalling in this HCT116 α1.S347A cell line confers hypersensitivity to growth inhibition by metformin. Complementary chemical approaches confirmed this relationship in both HCT116 and the genetically distinct HT29 colorectal cells, as AMPK activators imposed vulnerability to growth inhibition by metformin in both lines. Growth inhibition by metformin was abolished when AMPKα1 kinase was deleted. We conclude that elevated AMPKα1 activity modifies the signalling architecture in such a way that metformin treatment compromises cell proliferation. Not only does this mutant HCT116 AMPKα1-S347A line offer an invaluable resource for future studies, but our findings suggest that a robust biomarker for chronic AMPKα1 activation for patient stratification could herald a place for the well-tolerated drug metformin in colorectal cancer therapy.